2022
DOI: 10.1038/s41598-022-12906-x
|View full text |Cite
|
Sign up to set email alerts
|

The electrical signature of mafic explosive eruptions at Stromboli volcano, Italy

Abstract: Volcanic lightning is commonly observed in explosive volcanic eruptions of Volcanic Explosivity Index (VEI) > 2 and can be detected remotely providing real-time volcano monitoring information. However, little is known about the electrical activity accompanying the lower-magnitude spectrum of explosive eruptions, often involving mafic magmas. We narrow this gap in knowledge by presenting the electrical signature of the explosive activity (VEI ≤ 1) of Stromboli volcano (Italy) recorded by an electrostatic thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
(101 reference statements)
3
6
1
Order By: Relevance
“…Since the electric field decreases proportional to the distance cubed from the discharge location, it seems that magnitude of the discharges was too small to be picked up by the more distant sensors. This supports the findings of Vossen et al [2022] that electrical discharges can occur also during low VEI activity, as it is common during normal Strombolian explosions and further highlights the necessity of near-vent instrumentation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Since the electric field decreases proportional to the distance cubed from the discharge location, it seems that magnitude of the discharges was too small to be picked up by the more distant sensors. This supports the findings of Vossen et al [2022] that electrical discharges can occur also during low VEI activity, as it is common during normal Strombolian explosions and further highlights the necessity of near-vent instrumentation.…”
Section: Discussionsupporting
confidence: 88%
“…We propose that these signals were linked to (inaudible) ash venting or ash-rich puffing from a different vent prior to the explosion at the S1 vent. In this case, electrical signals can be generated in the rising ash plume even after the acoustic event (explosion) has ceased [Vossen et al 2022]. The acoustic events could be identified in all datasets, confirming the events (see Figure 4A and B).…”
Section: Discussionsupporting
confidence: 65%
“…Vent discharges are hypothesized to be a form of streamer discharge (Behnke et al 2018 , 2021 ), rather than full-fledged lightning. Recent observations have shown that vent discharges commence before large-scale charge separation develops in the eruption column (Behnke et al 2018 ) and that they may be enabled by the reduced atmospheric electric breakdown threshold in the near-vent region resulting from the propagation of shock waves (Méndez Harper et al 2018 ; von der Linden et al 2021 ). Vent discharges are correlated with the intensity of explosions (Smith et al 2020 , 2021 ) in which magma fragmentation and particle comminution occur (Smith et al 2018a ).…”
Section: Detection and Characteristics Of Volcanic Lightningmentioning
confidence: 99%
“…They create opportunities to monitor and characterize vent properties in real time (Cimarelli & Genareau, 2022). Spectacular recent examples include the eruptions of Eyjafjallajökull in 2010 (Bennett et al., 2010), Calbuco in 2015 (Van Eaton et al., 2016), ongoing Sakurajima eruptions (e.g., Aizawa et al., 2016; Cimarelli et al., 2016; Vossen et al., 2021), Bogoslof in 2016–2017 (Van Eaton et al., 2020), Anak Krakatau in 2018 (Prata et al., 2020), Stromboli in 2019 (Vossen et al., 2022), and Hunga Tonga‐Hunga Ha'apai in 2022 (Yuen et al., 2022).…”
Section: Introductionmentioning
confidence: 99%